STATISTICAL ANALYSIS AND FORECASTING OF RAIL TRANSPORT ACCIDENTS IN THE CZECH REPUBLIC - Motyková, Jana; Švadlenka, Libor (STEF92 Technology Ltd., 2016)
Transport accidents are significant components of the crisis management of every transport services provider. Safety in transport has gained increasing importance over the last few years. The Transport Policy of the Czech Republic for 2014 – 2020 with the Prospect of 2050 defines the goals determining process of traffic safety development. This paper will be focused on rail transport, especially on accidents. Rail transport is an important part of the transport system in the Czech Republic because of the railway infrastructure’s density. In the monitored period 2008 – 2015 the accidents in rail transport had relatively declining trend. The aim of this article is to analyze accidents in rail transport in the Czech Republic in the period 2008 – 2015 and forecast future course for the year 2016. In the first step it will be recognized the seasonal trend of the time series of accidents in rail transport. In case that the time series will have a seasonal component, it must be cleaned of its impact. After seasonal analysis will be investigated the trend component of the time series by the growth characteristics, the chart analysis and the Theil’s coefficient. If the time series would include the trend component, we should be able to forecast the accidents in rail transport for the year 2016.
Statistická analýza a prognózování mimořádných událostí v železniční dopravě v České republice
Keywords: safety; accidents; rail transport; time series; bezpečnost; mimořádné události; železniční doprava; časová řada